Relation of fetal growth to adult lung function in south India. Issue 10 (October 1997) - Stein, C E; Kumaran, K; Fall, C H; Shaheen, S O; Osmond, C; Barker, D J
Abstract : BACKGROUND: Follow up studies in Britain have shown that low rates of fetal growth are followed by reduced lung function in adult life, independent of smoking and social class. It is suggested that fetal adaptations to undernutrition in utero result in permanent changes in lung structure, which in turn lead to chronic airflow obstruction. India has high rates of intrauterine growth retardation, but no study has examined the association between fetal growth and adult lung function in Indian people. We have related size at birth to lung function in an urban Indian population aged 38-59 years. METHODS: Two hundred and eighty six men and women born in one hospital in Mysore City, South India, during 1934-1953 were traced by a house-to-house survey of the city. Their mean forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) were measured using a turbine spirometer. These measurements were linked to their size at birth, recorded at the time. RESULTS: In both men and women mean FEV1 fell with decreasing birthweight. Adjusted for age and height, it fell by 0.09 litres with each pound (454 g) decrease in birthweight in men (95% confidence interval (CI) 0.01 to 0.16) and by 0.06 (95% CI -0.01 to 0.13) in women. Likewise, mean FVC fell by 0.11 litres (95% CI 0.02 to 0.19) with each pound decrease in birthweight in men, and by 0.08 litres (95% CI 0.002 to 0.16) in women. FEV1 and FVC were lower in men who smoked, but the associations with size at birth were independent of smoking. Small head circumference at birth was associated with a low FEV1/FVC ratio in men which may reflect restriction in airway growth in early gestation. CONCLUSION: This is further evidence that adult lung function is "programmed" in fetal life. Smoking may be particularly detrimental to the lung function of populations already disadvantaged by poor rates of fetal growth.